Pedagogical Content Knowledge in STEM Research to Practice - Uzzo, Stephen Miles; Graves, Sherryl Browne; Shay, Erin.; Harford, Marisa; Thompson, Robert; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This volume represents both recent research in pedagogical content knowledge (PCK) in science, technology, engineering and math (STEM), as well as emerging innovations in how PCK is applied in practice. The notion of (3z(Bresearch to practice(3y (Bis critical to validating how effectively PCK works within the clinic and how it can be used to improve STEM learning. As the need for more effective educational approaches in STEM grows, the importance of developing, identifying, and validating effective practices and practitioner competencies are needed. This book covers a wide range of topics in PCK in different school levels (middle school, college teacher training, teacher professional development), and different environments (museums, rural). The contributors believe that vital to successful STEM education practice is recognition that STEM domains require both specialized domain knowledge as well as specialized pedagogical approaches. The authors of this work were chosen because of their extensive fieldwork in PCK research and practice, making this volume valuable to furthering how PCK is used to enlighten the understanding of learning, as well as providing practical instruction. This text helps STEM practitioners, researchers, and decision-makers further their interest in more effective STEM education practice, and raises new questions about STEM learning.s
Section 1: PCK Research in Formal Teaching Practice -- Analysis of Practice and Teacher PCK: Inferences from Professional Development Research -- The intertwined roles of teacher content knowledge and knowledge of scientific practices in support of a science learning community -- Personal and Canonical PCK: A Synergistic Relationship? -- From Budgets to Bus Schedules: Contextual Barriers and Supports for Science Instruction in Elementary Schools -- Teacher Knowledge and Visual Access to Mathematics -- Section 2: PCK in Formal Pre-Service Teacher Learning -- Teacher Inquiry as a Vehicle for Developing Pedagogical Content Knowledge in Pre-service Teachers. -- Biology Teacher Preparation and PCK: Perspectives from the discipline -- Pedagogical Content Knowledge in a Mathematics Adolescent Education Master of Arts Program: A Case Study -- Evaluation of PCK in STEM Residency Programs: Challenges and Opportunities -- Section 3: PCK in Informal Learning -- Pre-Service Teachers Developing PCK in a Natural History Museum -- Engineering STEM Teacher Learning: Using Design-Make-Play to develop disciplinary teaching knowledge -- Collaborative PCK in Practice: Bringing Together Secondary, Tertiary and Informal Learning in a STEM Residency Program -- Developing Educative Materials to Support Middle School Science Teachers' PCK for Argumentation: Comparing Multimedia to Text-based Supports -- Teacher Education for Maker Education: Helping teachers develop appropriate PCK for engaging children in educative making -- Index.
Keywords: Science -- Study and teaching; Mathematics; Science Education; Societal Aspects of Physics, Outreach and Education; Mathematics Education; Teaching and Teacher Education